I like your style an analysis of differences and similarities in conversational style of selected senior high school students from Sto. Niño Catholic School - Go, Myka V. (College of Arts and Letters, University of the Philippines Diliman, 2008)
This study explored differences and similarities in the conversational styles of selected male and female senior high school students in a same-sex group and mixed-sex group. The frameworks that were used in this study were Conversational Analysis, the SPEAKING mnemonic and Tannen's genderlect theory. Conversations of selected male and female senior high school students from Sto. Niño Catholic School during lunch were recorded and the conversational styles of the participants were analyzed by closely examining turn-taking, topic initiation, acknowledgement tokens, speeding up, and slowing down. After identifying and describing the participants' conversational styles, the results were compared and contrasted to find out if there are differences and/or similarities in the features identified and described. The collected conversations examined show the similar features of conversational style were used by the participants in different instances and in different frequencies in a conversation regardless of whether they were in the all-female, all-male, and mixed-sex group. Similar strategies of topic initiation and backchannels were also observed in participants. This study shows that features of conversational style may not be categorized according to gender because the occurrence of these features vary from person to person: however, differences were seen when the frequency of deployment and usage of the conversational style features were tabulated.